2009
DOI: 10.1088/1742-6596/150/3/032025
|View full text |Cite
|
Sign up to set email alerts
|

Torsional oscillators and the entropy dilemma of putative supersolid4He

Abstract: Solid 4 He is viewed as a nearly perfect Debye solid. Yet, recent calorimetry measurements by the PSU group (J. Low Temp. Phys. 138, 853 (2005) and Nature 449, 1025 (2007)) indicate that at low temperatures the specific heat has both cubic and linear contributions. These features appear in the same temperature range where measurements of the torsional oscillator period suggest a supersolid transition. We analyze the specific heat and compare the measured with the estimated entropy for a proposed supersolid tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 20 publications
1
26
1
Order By: Relevance
“…Our results show that the low-temperature deviations in the measured specific heat can be explained by contributions from a glassy fraction of the solid. These results add further support to our previous interpretation of torsion oscillator experiments in terms of a backaction due to a glassy subsystem, which is possibly present in solid 4 He [38,37,39]. …”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results show that the low-temperature deviations in the measured specific heat can be explained by contributions from a glassy fraction of the solid. These results add further support to our previous interpretation of torsion oscillator experiments in terms of a backaction due to a glassy subsystem, which is possibly present in solid 4 He [38,37,39]. …”
Section: Introductionsupporting
confidence: 89%
“…This enormous discrepancy between supersolid fractions in specific heat and torsion oscillator experiments was already noticed in Refs. [36,37]. Until to date, this discrepancy remains a major puzzle that is hard to reconcile within a purely supersolid scenario.…”
Section: Entropy Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. 44, it is claimed that specific-heat measurements are contrary to entropy predictions based on a Bose-Einstein type of supersolidity, however, we may see that in our GinzburgLandau model there is no such problem. 3 is of the order of 10 −4 .…”
Section: A Entropy Of the Supersolid Partcontrasting
confidence: 71%
“…Nussinov et al 30 and Graf et al 37 have carried out much more sophisticated analyses of observed TO responses with generalized rotational susceptibilities expressing glassy response. They found that various single frequency TO responses in both dissipation and frequency shift could be fitted by appropriately adjusting parameters in the glassy response model.…”
Section: −1mentioning
confidence: 99%